Faktor-Faktor yang Mempengaruhi Pertumbuhan Sektor Pariwisata dan Dampaknya terhadap Ekonomi Kota Bandar Lampung - Hasbullah Hasbullah; Desmon Desmon (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Tourism in Bandar Lampung City has significant potential that has not been fully utilized. This study aims to analyze the factors influencing the growth of the tourism sector and its impact on the local economy. The research uses a qualitative method, with data collected through in-depth interviews with stakeholders, including tourism business operators, local government officials, and tourists. The data were analyzed using a thematic approach to explore patterns and relationships between factors. The findings show that consistent government policies, adequate infrastructure development, and digital-based tourism promotion play a key role in driving the growth of the tourism sector. The economic impacts include an increase in Local Revenue (PAD) and the creation of new job opportunities. This study recommends the sustainable development of the tourism sector through policies that support infrastructure improvement and digital promotion. In conclusion, the tourism sector in Bandar Lampung City has the potential to make a significant contribution to the local economy if optimally managed.